Effects of added nutrients and salinity on freshwater ecosystems - Kayla D. Coldsnow; Scott R. Goeppner; Rick A. Relyea (Environmental Pollution, 2026)

Additive effects of freshwater salinization on the predator-induced traits of larval amphibians - Bailey Tator; Mitchell Le Sage; Rick A. Relyea (Environmental Pollution, 2025)

Shedding Some Light on Lake Communities: Impacts of Light Level and Light Variability - Aaron B. Stoler; Kayla Coldsnow; Rick A. Relyea (Wetlands, 2025)

Salinization and low-dose levels of pesticides alter brain shape of larval amphibians - Sarah K. Woodley; Gabriela Agostini; Devin K. Jones; Rick A. Relyea (Environmental Pollution, 2024)

Effects of amphibian genetic diversity on ecological communities - Michael F. Benard; David J. Burke; Sarah R. Carrino-Kyker; Katherine Krynak; Rick A. Relyea (Oecologia, 2024)

A sequence of weather‐driven hydrodynamic events stimulates the formation of harmful algal blooms on an oligotrophic lake - Michael R. Kelly; Vincent W. Moriarty; Harry R. Kolar; Guillaume A. R. Auger; Michael E. Henderson; Campbell D. Watson; Rick A. Relyea; Christopher A. Scholz; Charles T. Driscoll; Kevin C. Rose (Limnology and Oceanography, 2024)
Harmful algal blooms (HABs) are common in many eutrophic lakes and frequently associated with nutrient excesses, warm waters, and calm conditions. While HABs can also occur in oligotrophic waterbodies, bloom‐stimulating factors remain elusive for these ecosystems. Here, using a high‐frequency sensor platform supported by hydrodynamic modeling, we document a clearly linked sequence of three hydrodynamic events that immediately preceded each HAB event on Skaneateles Lake, NY during 2018. HABs were first preceded by interactions between internal waves in the thermal structure of the lake with the northern slope of the lakebed. These interactions disturbed sediments resulting in upwelling of nutrient‐rich sediment and possibly cyanobacterial cells into the lower water column. Next, moderate winds stimulated Langmuir circulation which facilitated the transport of material from the lower water column to well‐lit surface waters. Finally, the sequence culminated with a calm wind period, which is often classically associated with surface HAB formation. While individual steps in this sequence occurred independently and repeatedly throughout the year, the complete sequence occurred only eight times, immediately preceding each of the eight documented HABs. We empirically derive thresholds for and timing of the sequence to independently predict HAB occurrence and elevated cyanobacteria levels in the lake. The discovery of this specific and repeated event sequence and the identified thresholds provides the potential for forecasting of HABs days in advance. Ongoing climate change impacts, including increasing water column thermal stratification and changing wind speeds may alter the frequency, timing, and duration of this sequence and consequent HAB formation.

Naïve and induced tolerance of 15 amphibian populations to three commonly applied insecticides - Devin K. Jones; Devin G. DiGiacopo; Brian M. Mattes; Erika Yates; Jessica Hua; Jason T. Hoverman; Rick A. Relyea (Aquatic Toxicology, 2024)

Considering sub-basins in the spatio-temporal dynamics of lake food webs - Jonathan J. Borrelli; Matthew S. Schuler; William D. Hintz; Brian Mattes; Candace Schermerhorn; Erika Yates; Lawrence W. Eichler; Mark A. Lucius; Laurie Ahrens; Rick A. Relyea (Aquatic Sciences, 2024)

Putting a lake together: Integrating synthetic data and field observations to build a better food web - Jonathan J. Borrelli; Matthew S. Schuler; William D. Hintz; Mary Alldred; Brian Mattes; Candace Schermerhorn; Erika Yates; Lawrence W. Eichler; Mark A. Lucius; Rick A. Relyea (Food Webs, 2023)

Phenotypically plastic responses to freshwater salinization in larval amphibians: Induced tolerance and induced sensitivity - Rick A. Relyea; Candace X. Schermerhorn; Brian M. Mattes; Isaac D. Shepard (Environmental Pollution, 2023)

Population-level variation in insecticide tolerance across three life stages of the trematode Echinostoma trivolvis - Logan S. Billet; Vanessa P. Wuerthner; Rick A. Relyea; Jason T. Hoverman; Jessica Hua (Aquatic Toxicology, 2023)

A review of spatial structure of freshwater food webs: Issues and opportunities modeling within‐lake meta‐ecosystems - Jonathan J. Borrelli; Rick A. Relyea (Limnology and Oceanography, 2022)
Lakes are currently facing multiple anthropogenic stressors impacting their ecological communities. The best way to understand how these systems will be affected by the changing environment is by modeling community dynamics. Models of lake food webs have tended to focus on pelagic organisms and treat lakes as if they contain single, uniform communities. However, heterogeneity in environmental conditions and resource availability generates within‐lake compartmentalization in food web structure. Turnover among species and their interactions resulting from differences in depth and substrate type creates unique food webs in different regions of lakes. Food webs within lakes can therefore be represented as a three‐dimensional meta‐ecosystem, where food web compartments are connected by flows of nutrients, materials, and consumers with variable degrees of mobility within the lake. We review how food webs are spatially structured within lakes and the processes that connect different parts of the ecosystem. We then discuss how current modeling approaches address the spatial heterogeneity of lake communities, highlighting key methods and some of the constraints preventing more spatially explicit representation of food webs. Finally, we recommend the use of allometric trophic networks to make spatially explicit food web modeling easier. By capitalizing on empirically described allometric relationships to parameterize trophically complex food webs, we can balance generalizable model approaches with system‐specific needs. Given the spatially explicit nature of many current threats to freshwater lakes, building an understanding of how space structures the community is imperative to create better approaches for freshwater management and conservation.

Seasonal diatom community responses to development and climate change in Lake George, an oligotrophic lake in the Adirondack Mountains - Adam T. Ruka; Jeffrey R. Johansen; Jan Leps; Zachary J. Loken; Matt Schuler; Brian Mattes; Erika Yates; Rick A. Relyea (Hydrobiologia, 2022)

Calcium chloride pollution mitigates the negative effects of an invasive clam - Kayla D. Coldsnow; William D. Hintz; Matthew S. Schuler; Aaron B. Stoler; Rick A. Relyea (Biological Invasions, 2021)

Effects of invasive larval bullfrogs (Rana catesbeiana) on disease transmission, growth and survival in the larvae of native amphibians - Andrew R. Blaustein; Devin K. Jones; Jenny Urbina; Ricky D. Cothran; Carmen Harjoe; Brian Mattes; Julia C. Buck; Randall Bendis; Trang Dang; Stephanie S. Gervasi; Rick Relyea (Biological Invasions, 2020)
The mechanisms by which invasive species negatively affect native species include competition, predation, and the introduction of novel pathogens. Moreover, if an invasive species is a competent disease reservoir, it may facilitate the long-term maintenance and spread of pathogens in ecological assemblages and drive the extinction of less tolerant or less resistant species. Disease-driven loss of biodiversity is exemplified by the amphibian–chytrid fungus system. The disease chytridiomycosis is caused by the aquatic chytrid fungus Batrachochytrium dendrobatidis (Bd) in anurans and is associated with worldwide amphibian population declines and extinctions. For amphibian species that metamorphose and leave infected aquatic habitats, the mechanisms by which Bd persists over winter in these habitats remains a critical open question. A leading hypothesis is that American bullfrogs ( Rana catesbeiana ), a worldwide invasive species, are tolerant to Bd and serve as a reservoir host for Bd during winter months and subsequently infect native species that return to breed in spring. Using outdoor mesocosms, we experimentally examined if two strains of Bd could overwinter in aquatic systems, in the presence or absence of bullfrog tadpoles, and if overwintered Bd could be transmitted to tadpoles of two spring-breeding species: Pacific treefrogs ( Pseudacris regilla ) and Cascades frogs ( Rana cascadae ). We found that only 4 of 448 total animals (one bullfrog and three spring breeders) tested positive for Bd after overwintering. Moreover, two of the three infected spring breeders emerged from tanks that contained overwintered Bd but in the absence of infected bullfrogs. This suggests that Bd can persist over winter without bullfrogs as a reservoir host. We found no effect of Bd strain on bullfrog survival after overwintering. For Pacific treefrogs, Bd exposure did not significantly affect mass at or time to metamorphosis while exposure to bullfrogs reduced survival. For Cascades frogs, we found an interactive effect of Bd strain and bullfrog presence on time to metamorphosis, but no main or interactive effects on their survival or mass at metamorphosis. In short, bullfrog tadpoles rarely retained and transmitted Bd infection in our experiment and we found limited evidence that Bd successfully overwinters in the absence of bullfrog tadpoles and infects spring-breeding amphibians.

Concurrent improvement and deterioration of epilimnetic water quality in an oligotrophic lake over 37 years - William D. Hintz; Matthew S. Schuler; Jonathan J. Borrelli; Lawrence W. Eichler; Aaron B. Stoler; Vincent W. Moriarty; Laurie E. Ahrens; Charles W. Boylen; Sandra A. Nierzwicki‐Bauer; Rick A. Relyea (Limnology and Oceanography, 2020)
Single‐lake studies offer an opportunity for understanding, predicting, and mitigating local or regional threats to lake ecosystems. Our goal was to understand how concurrent environmental stressors such as climate change, eutrophication, and salinization affect long‐term lake water quality. We report epilimnetic changes in 18 water‐quality parameters collected at seven sites from 1980 to 2016 in Lake George, a large oligotrophic lake in the Adirondack Park, New York, USA. Improvements and deteriorations in water quality occurred over 37 years. We observed a 32% increase in chlorophyll a associated with an increase in orthophosphate, but not total phosphorus or a warming epilimnion (0.05°C/year). Salinization from road deicing salts contributed to the largest deterioration in water quality. However, chloride concentrations and the current rate of increase are low enough that few ecological impacts are likely to occur over the next few decades. Increasing calcium concentrations were not high enough to facilitate the persistence of invasive species in the lake such as zebra mussels ( Dreissena polymorpha ) but are sufficient for Asian clams ( Corbicula fluminea ) and the spiny water flea ( Bythotrephes longimanus ). Similar to other lakes, environmental legislation has supported recovery from acidification, indicated by reduced sulfate and nitrate, and increased alkalinity and pH. Declines in water quality were minor relative to other lakes, suggesting that decades of tourism and development occurred without major deterioration in water quality, but management efforts are needed to curb salinization in the Lake George watershed, particularly as it relates to sodium concentrations to prevent a loss of drinking water quality.

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

A salty landscape of fear: responses of fish and zooplankton to freshwater salinization and predatory stress - William D. Hintz; Rick A. Relyea (Oecologia, 2017)

Litter chemistry and chemical diversity drive ecosystem processes in forest ponds - Aaron B. Stoler; David J. Burke; Rick A. Relyea (Ecology, 2016)
Research suggests that a positive relationship exists between diversity and ecological function, yet the multi‐trophic effects of biodiversity remain poorly understood. The resource complementarity hypothesis suggests that increasing the trait diversity of resources provides a more complete diet for consumers, elevating consumer feeding rates. Whereas previous tests of this mechanism have measured trait diversity as the variation of single traits or the richness of functional groups, we employed a multivariate trait index to manipulate the chemical diversity of temperate tree litter species in outdoor pond mesocosms. We inoculated outdoor mesocosms with diverse and multi‐trophic communities of microbial and macro‐consumer species that rely on leaf litter for energy and nutrients. Litter was provided at three levels of chemical trait diversity, a constant level of species richness, and an equal representation of all litter species. Over three months, we measured more than 65 responses, and assessed the effects of litter chemical diversity and chemical trait means (i.e., community‐weighted means). We found that litter chemical diversity positively correlated with decomposition rate of leaf litter, but had no effect on biomass or density of producers and consumers. However, the pond communities often responded to chemical trait means, particularly those related to nutrients, structure, and defense. Our results suggest that resource complementarity does have some effect on the release of energy and nutrients from decomposing substrates in forest ponds, but does not have multi‐trophic effects. Our results further suggest that loss of tree biodiversity could affect forest ecosystem functionality, and particularly the processes occurring in and around ponds and wetlands.

Wetland defense: naturally occurring pesticide resistance in zooplankton populations protects the stability of aquatic communities - Randall J. Bendis; Rick A. Relyea (Oecologia, 2016)

Dissecting the smell of fear from conspecific and heterospecific prey: investigating the processes that induce anti-predator defenses - Heather M. Shaffery; Rick A. Relyea (Oecologia, 2016)

Leaf litter resource quality induces morphological changes in wood frog (Lithobates sylvaticus) metamorphs - Aaron B. Stoler; Jeffrey P. Stephens; Rick A. Relyea; Keith A. Berven; Scott D. Tiegs (Oecologia, 2015)

Exposure to sublethal concentrations of a pesticide or predator cues induces changes in brain architecture in larval amphibians - Sarah K. Woodley; Brian M. Mattes; Erika K. Yates; Rick A. Relyea (Oecologia, 2015)

An empirical test of stable species coexistence in an amphipod species complex - Rickey D. Cothran; Patrick Noyes; Rick A. Relyea (Oecologia, 2015)

Sex-specific plasticity in body phosphorus content of Hyalella amphipods - Jared M. Goos; Beverly J. French; Rick A. Relyea; Rickey D. Cothran; Punidan D. Jeyasingh (Hydrobiologia, 2014)

Bottom-up meets top-down: leaf litter inputs influence predator–prey interactions in wetlands - Aaron B. Stoler; Rick A. Relyea (Oecologia, 2013)

Reproductive interference via interspecific pairing in an amphipod species complex - Rickey D. Cothran; Andy R. Stiff; Kristopher Chapman; Gary A. Wellborn; Rick A. Relyea (Behavioral Ecology and Sociobiology, 2013)

Leaf litter quality induces morphological and developmental changes in larval amphibians - Aaron B. Stoler; Rick A. Relyea (Ecology, 2013)
Aquatic consumers exhibit many types of inducible phenotypic responses to variation in resource quantity and quality. Leaf litter constitutes a primary resource in freshwater systems, and variation in litter quality can alter the growth and development of aquatic consumers. It is therefore reasonable to hypothesize that variation in litter quality might also induce phenotypic changes in consumers. To test this hypothesis, we exposed two densities of wood frog ( Lithobates sylvaticus [ Rana sylvatica ]) tadpoles to six chemically distinct species of leaf litter from temperate broadleaf and coniferous trees. After several weeks, we quantified development rate, growth rate, intestinal length, size of the oral disc, and five external dimensions of the tadpoles. In addition to substantial changes in growth and development rates, we found striking changes in all morphological responses among different leaf litter environments, including up to 14% longer intestines, 11% deeper tails, and 6% deeper tail muscles. In addition, we found strong relationships of total nitrogen content with all morphological features except growth rate. Our results indicate that differences in resource quality can induce phenotypic changes that are as large as or larger than changes induced by resource quantity. Our study also has substantial implications for the future of aquatic consumers living in forested wetlands given that these forests are currently experiencing widespread changes in tree composition.

"Cryptic" direct benefits of mate choice: choosy females experience reduced predation risk while in precopula - Rickey D. Cothran; Kristopher Chapman; Andy R. Stiff; Rick A. Relyea (Behavioral Ecology and Sociobiology, 2012)

Adaptive plasticity in predator-induced defenses in a common freshwater snail: altered selection and mode of predation due to prey phenotype - Josh R. Auld; Rick A. Relyea (Evolutionary Ecology, 2011)

Life-history plasticity and inbreeding depression under mate limitation and predation risk: cumulative lifetime fitness dissected with a life table response experiment - Josh R. Auld; Rick A. Relyea (Evolutionary Ecology, 2010)

A cocktail of contaminants: how mixtures of pesticides at low concentrations affect aquatic communities - Rick A. Relyea (Oecologia, 2009)

Metacommunity patterns in larval odonates - Shannon J. McCauley; Christopher J. Davis; Rick A. Relyea; Kerry L. Yurewicz; David K. Skelly; Earl E. Werner (Oecologia, 2008)

Detecting small environmental differences: risk-response curves for predator-induced behavior and morphology - Nancy M. Schoeppner; Rick A. Relyea (Oecologia, 2008)

The rules of engagement: how to defend against combinations of predators - Jason T. Hoverman; Rick A. Relyea (Oecologia, 2007)

Getting out alive: how predators affect the decision to metamorphose - Rick A. Relyea (Oecologia, 2007)

Assessing the ecology in ecotoxicology: a review and synthesis in freshwater systems - Rick Relyea; Jason Hoverman (Ecology Letters, 2006)
The field of ecotoxicology is experiencing a surge in attention among ecologists as we gain a deeper appreciation for how contaminants can impact natural ecosystems. This interest is particularly strong in aquatic systems where many non‐target organisms experience pesticides. In this article, we assess how pesticides affect freshwater systems by applying the conceptual framework of density‐ and trait‐mediated indirect effects from the field of basic ecology. We demonstrate the utility of this framework for understanding the conditions under which pesticides affect species interactions, communities and ecosystems. Through the integration of laboratory toxicity tests and this ecological framework, ecotoxicologists should be better able to identify the mechanisms through which pesticides affect communities and ecosystems. We also identify several areas of research that are in critical need of empirical attention including synergistic effects between pesticides and natural stressors, the importance of pesticides on community assembly via habitat preferences and oviposition effects, the timing and frequency of pesticide applications, pesticide effects on population dynamics, the evolution of pesticide resistance in non‐target organisms and ecosystem recovery. With this knowledge, one can improve upon management decisions and help protect non‐target species that are of conservation concern.

The effects of pesticides, pH, and predatory stress on amphibians under mesocosm conditions - Rick A. Relyea (Ecotoxicology, 2006)

Classification of wetlands in a Patagonian National Park, Chile - John C. Clausen; Isaac M. Ortega; Christine M. Glaude; Rick A. Relyea; Gladys Garay; Oscar Guineo (Wetlands, 2006)

Damage, digestion, and defence: the roles of alarm cues and kairomones for inducing prey defences - Nancy M. Schoeppner; Rick A. Relyea (Ecology Letters, 2005)
Inducible defences are widely used for studying phenotypic plasticity, yet frequently we know little about the cues that induce these defences. For aquatic prey, defences are induced by chemical cues from predators (kairomones) and injured prey (alarm cues). Rarely has anyone determined the separate and combined effects of these cues, particularly across phylogenetically diverse prey types. We examined how tadpoles ( Hyla versicolor ) altered their defences when 10 different prey were either crushed by hand or consumed by predators. Across all prey types, crushing induced only a subset of the defences induced by consumption. Consuming vs. crushing produced additive responses for behaviour but synergistic responses for morphology and growth. Moreover, we discovered the first extensive evidence that prey responses to different alarm cues depends on prey phylogeny. These results suggest that the amount of information available to the prey affects both the quantitative and qualitative nature of the defended phenotype.

Having the guts to compete: how intestinal plasticity explains costs of inducible defences - Rick A. Relyea; Josh R. Auld (Ecology Letters, 2004)
Predators commonly induce phenotypic changes that make prey better at surviving predation at the cost of reduced growth. While we have a good understanding of how trait changes affect predation risk, we lack a mechanistic understanding of why predator‐induced phenotypes differ in growth. Using two mesocosm experiments, we combined phenotypic plasticity theory with predictions from optimal digestion theory to demonstrate that intra‐ and interspecific competition induced relatively long guts while predators induced relatively short guts. The longer guts induced by competition appear to be an adaptive response that allows more efficient digestion and more rapid growth whereas the shorter guts induced by predators appear to result from a tradeoff of building larger tails in predator environments at the cost of smaller bodies. By combining these two bodies of theory, we now have a much better understanding of the mechanisms that cause the phenotypic trade‐offs that select for inducible defences.

Estimating Decline and Distributional Change in Amphibians - David K. Skelly; Kerry L. Yurewicz; Earl E. Werner; Rick A. Relyea (Conservation Biology, 2003)
Concern over species declines has prompted researchers to use historical data as a basis for comparison with present‐day information from the same sites to assess changes in presence/absence distributions. A review of the literature revealed that these resurveys typically lasted for 1 or 2 years, and many were based on museum records or other data relying on known historical presences. Using data on nine amphibian species from a set of 32 ponds at the E. S. George Reserve ( ESGR ) in Michigan, we evaluated the importance of the duration of a resurvey and the type of historical data used ( information on historical presences and absences vs. historical presences only ). We compared data we collected between 1996 and 2000 with information from the same ponds collected between 1967 and 1974. By systematically degrading the 1996–2000 data, we determined that a resurvey lasting 1 year would yield an estimated 45% decline in the number of presences, whereas a resurvey lasting 2 years would yield an estimated 28% decline. In contrast, a 5‐year resurvey would yield an estimated 3% decline in the number of presences. In addition, when our historical data were limited to known presences in the past, even a 5‐year resurvey yielded an estimated 30% decline in the number of presences. Our results suggest that estimates of decline and distributional change can be extremely sensitive to the duration of resurvey effort and the type of historical data used. The pattern we found in analyses of ESGR data is echoed in published studies in which multiple‐year resurveys tended to yield smaller estimates of decline than single‐year resurveys. Based on our findings, we suggest that future resurveys extend for long enough to estimate the value of additional data and that geographic scales of inference be chosen based on the amount and quality of historical information.

The impact of larval predators and competitors on the morphology and fitness of juvenile treefrogs - Rick A. Relyea; Jason T. Hoverman (Oecologia, 2003)

Predicting community outcomes from pairwise interactions: integrating density- and trait-mediated effects - Rick A. Relyea; Kerry L. Yurewicz (Oecologia, 2002)